Factors that determine donors intention to endow cash waqf for microenterprises in Malaysia - Abdul Razak, Dzuljastri; Fodol, Mohamed Zakaria; AIi, Ahmad Burhan; Ahmed, Abdilahi Jama (2018)
In the modern era Waqf concept has become more sophisticated and comprehensive and through it, many financial products and social programs were developed, for instance, Cash waqf and some securities paper such as shares-waqf, Sukuk-waqf, etc. Therefore, Cash waqf can also be used in microenterprises to efficiently channel funds (interest free-funds) to microenterprises to alleviate poverty and decrease the unemployment. Recently, several products for Cash waqf in microenterprises have been established, but they could not reach their targets, they need a significant contribution from Muslims in the society. Thus, lacuna exists to assess the intention of donners towards Cash waqf for Microenterprises empirically. Therefore, the paper aims to determine factors influencing intention to endow Cash waqf for Microenterprises based on four variables namely, concept of Cash waqf, trust, religiosity motivation, and social culture. The method was carried out the by survey of 200 respondents in Kuala Lumpur, Malaysia. Factor analysis, multiple regression, was used to estimate the relationship between variables. The result indicated that concept of Cash waqf, trust, and social culture have a significant relationship with the intention to endow CWME. Hence, practitioners can emphasize on the three factors in their marketing efforts to promote CWME. The academicians may benefit by conducting more research in this elegance frame of knowledge.